THE EFFECT OF CARBON NANOTUBE ADDITION ON NICKEL SULFIDE (NIS) MATERIALS FOR SUPERCAPACITOR AND ZINC ION BATTERY APPLICATION - Hanif Tejo Baskoro, Fakhrian
The increasing demand in energy drives the development of energy storage devices with high energy capacity and high energy throughput. Supercapacitors are energy storage devices that store charge on their surfaces, providing much greater power density compared to batteries as well as better cycle stability. Pseudocapacitors, as one type of supercapacitor, utilize the principle of surface redox reaction, providing better capacitance. One class of materials that has a pseudocapacitor principle is the transition metal sulfide which exhibit pseudocapacitive behavior owing to their high redox activity and reaction stability, with nickel sulfide as an example of a material capable of achieving high capacitance. On the other hand, zinc ion batteries have emerged as a developing battery technology recently due to their cost-effectiveness and environmental friendliness, where transition metal sulfides may become suitable materials for application as cathodes. Unfortunately, the low conductivity in the redox-based material impairs their capacitance performance at high currents and at a large number of cycles. Nanostructuring and addition of conductive materials are believed to improve the performance of pseudocapacitors. In this study, nickel sulfide material as a pseudocapacitor was composited with Carbon nanotubes (CNT) using the hot-injection method to demonstrate experimentally the effect of adding conductive material in enhancing the pseudocapacitor performance. The first step was to synthesize nickel sulfide without the addition of CNT and investigate its crystal structure and electrochemical properties. The results of X-ray Diffraction (XRD) characterization revealed the formation of a mixed phase of Ni3S2 and NiO. Furthermore, the Cyclic Voltammetry (CV) characterization of nickel sulfide samples deposited as supercapacitor electrodes and measured using a three-electrode setup show that there is a redox reaction, confirming the pseudocapacitive behavior of nickel sulfide. Based on the results of the Galvanostatic Charge-Discharge (GCD) characterization, the capacitance of the nickel sulfide sample was obtained at 794,06 F/g. Next, we added CNTs in a similar synthesis process with compositions of 10, 20, and 30wt% to determine the optimal composition of CNTs which were then deposited as electrodes and tested in a three-electrode setup. The CV characterization results still showed the presence of redox peaks, indicating the pseudocapacitance contributions in the NiS/CNT composite samples. Subsequently, the GCD characterization showed that the 20wt% NiS/CNT composition showed an increased charging-discharging time and through capacitance calculations it was proven that the sample had the highest capacitance of 1249,90 F/g, with a cycle stability of 94.14% at a current density of 3 A/g over 1500 cycles. Electrochemical impedance spectroscopy (EIS) characterization demonstrated enhanced charge transfer ease on the NiS electrode along with the addition of CNT as a conductive material. The NiS/CNT 20wt% sample, whick demonstrated the best performance, was then structurally analyzed. The results of the XRD characterization showed the involvement of carbon originating from CNT in the sample, as evidenced by the appearance of the (002) peak associated with carbon alongside others corresponding to Ni3S2 and NiO peaks. SEM characterization showed an irregular coral-like surface morphology with CNT decoration on part of its surfaces. As a zinc ion battery cathode, the NiS/CNT 20wt% demonstrated a specific capacity of 132.68 mAh/g, with an energy density of 204.20 Wh/kg at a power density of 1.89 W/kg. Based on the conducted research, it was found that the addition of CNT in general can enhance the performance of nickel sulfide pseudocapacitors. This is indicated by the increase in the capacitance value, with the highest improvement achieved by the NiS/CNT 20wt% sample. This research should be developed further by investigating reaction mechanisms with more advanced characterization and advancing supercapacitor and zinc ion batteries system into more applicable forms.